COMBINED METHOD OF LEARNING ANATOMY E-LEARNING AND CLASS ROOM TEACHING IS THE BEST METHOD - Dr Anup Shyamal.; Dr Akash Kusum Banerjee.; Dr Biswapriya Sinha; Dr Enakshi Ghosh; Dr Arunima Roy; Prof Nirmal Kumar Mandal. (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Anatomy is vast and most volatile subject in MBBS curriculum. Students remain in extreme confusion with the contents and information. They try to learn it from either class room teaching or from e-learning or from combined. Present study is based on a spontaneous feedback filled by students after completion of final examination of Anatomy. Marks obtained in theory and practical both for all the students were analyzed with their response on the feed back form. It results the mode of method for learning anatomy was favoured to combined method of learning Class room as well as E- learning combination is the best method for learning anatomy, not to consider in any single method.